Arctica islandica in Kiel Bay : body parameters, shell length-meat weight relationship and seasonality in flesh weight and condition index - Swaileh, Khalid (1999)
Ocean Quahogs, Arctica Islandica, were collected over one year on a monthly basis from Keil Bay, Western Baltic. The largest Quahog found during this study measured 75.1 mm. Statistically significant month to month variation in dry soft tissue weight and condition index were observed. The main period of increase in dry soft tissue weight was from May through September, Maximum weights were observed in September and minimum ones in March. The ratio between the two parameters was 2:1, respectively phytoplankton blooming and preparation for swapping.